Hubungan antara self efficacy dan dukungan sosial dengan pengambilan keputusan karir pada mahasiswa akhir - Amelia Cahya Kinasih; Nikmah Sofia Afiati; Narastri Insan Utami; Andini Dwian Putri (Universitas Muhammadiyah Metro, 2026)
Final-year students are in the early adulthood stage of development, transitioning from the academic world to the world of work. Final-year students are typically faced with various pressures such as the demand to graduate quickly and find the right career path. This study aims to determine the relationship between self-efficacy and social support with career decision-making in final-year students. The hypotheses proposed in this study are: there is a positive relationship between self-efficacy and career decision-making in final-year students; there is a positive relationship between social support and career decision-making in final-year students; and there is a positive relationship between self-efficacy and social support and career decision-making in final-year students. The number of participants in this study was 516 final-year students aged 19-25 from various universities. This research uses a quantitative approach with a research design. The analysis techniques used in this study are Pearson correlation test and multiple regression. The research results indicate that self-efficacy and social support have a significant relationship with career decision-making in final-year students (R = 0.448; R: 0.201; F: 643; P<0.001), meaning that the two variables explain 20.1% of the variation in career decision-making. This research confirms that self-efficacy and social support from the surrounding environment play an important role in helping final-year students determine their career goals and decisions after graduation.